Perbedaan Kelengkapan Pengisian Lembar Keperawatan Berdasarkan Shift Kerja Di Ruang Rawat Inap RSUD dr. Soeratno Gemolong Tahun 2016 - Muslimah, Ikhwanul, Heru Subaris Kasjono, SKM, M.Kes, Yuli Kusumawati, SKM, M. K es (Epid) (2016)
Inpatient care at hospitals required nursing resources that work shift. Nurses who work in shifts potentially get fatigue resulting in lower performance in filling 7 sheet of nursing documentation. Figures late return of documents amounted to 66.67%, and 63% incomplete documents from the night shift. This study was to determine differences in completeness of nursing sheet based on shifts in the inpatient unit of dr.Soeratno Gemolong. It was observational analytic cross sectional study. This study located at medical record installation of dr.Soeratno Gemolong. Sample of this study was 277 samples from 901 medical records document used proportional random sampling by taking systematic random sampling. Data Analysis used Kruskal Wallis test. The results showed that no difference between the completeness of shift work on Vital Signs sheet (p = 0.001), disease progression sheet (p=0,001), progression note (p=0,001), nurse information (p=0,001), and nursing resume (0,001). There was not difference completeness pharmacological therapy sheet (p = 0.058) and assessment nursing sheet (p=0,488) between shift works. The conclusion of this study showed from seven sheet of nursing documentation there was five sheets with different completeness of documentation. It requaired distribution of workload, rotational shift work, and working time nurse